DDR1 and MT1-MMP Expression Levels Are Determinant for Triggering BIK-Mediated Apoptosis by 3D Type I Collagen Matrix in Invasive Basal-Like Breast Carcinoma Cells - Saby, Charles; Collin, Guillaume; Sinane, Maha; Buache, Emilie; Van Gulick, Laurence; Saltel, Frédéric; Maquoi, Erik; Morjani, Hamid (Frontiers in Pharmacology, 2019)
Type I collagen is the major adhesive component in breast interstitial stroma, which represents the first barrier against tumor cell invasion after basement-membrane degradation. Among cellular receptors, type I collagen is able to activate discoidin domain receptors DDR1 and DDR2. We have previously shown that in 3D collagen matrix, DDR1 plays a key role as it promotes cell growth suppression and apoptosis through the upregulation of the pro-apoptotic mediator BIK in noninvasive luminal-like breast carcinoma cells. We have also shown that MT1-MMP is able to rescue these cells and protect them against the effects induced by collagen/DDR1/BIK axis. Our data suggested that the protective effect of MT1-MMP might be mediated through the degradation of type I collagen and/or DDR1 cleavage. Decreased DDR1 expression has been associated with the epithelial to mesenchymal transition process in breast cancer, and its overexpression in aggressive basal-like breast cancer cells reduces their invasiveness in 3D cultures and in vivo. In the present work, we propose to study the role of MT1-MMP in the resistance against collagen-induced apoptosis in basal-like breast carcinoma MDA-MB-231 cells. We aimed to investigate whether MT1-MMP depletion is able to restore apoptosis mediated by collagen/DDR1/BIK axis and to verify if such depletion is able to restore full-length DDR1 expression and phosphorylation. ShRNA strategy against MT1-MMP mRNA was able to partially restore full length DDR1 expression and phosphorylation. This was accompanied by a decrease in cell growth and an upregulation of BIK expression. This suggested that MT1-MMP expression in basal-like breast carcinoma cells, in addition to a low basal level of DDR1 expression, protects these cells against collagen-induced apoptosis via DDR1 cleavage. Since DDR1 was moderately expressed in MDA-MB-231 cells, we then investigated whether overexpression of DDR1 could be able to increase its ability to suppress cell growth and to induce apoptosis. Data showed that overexpression of DDR1 induced a decrease in cell growth and an increase in BIK expression, suggesting that moderate expression level of full length DDR1 in basal-like breast carcinoma provides them with a capacity to resist to collagen-induced cell growth suppression and apoptosis. Finally, the combined overexpression of DDR1 and depletion of MT1-MMP in MDA-MB-231 cells synergistically increased collagen-induced cell growth suppression and apoptosis to a level similar to that observed in luminal breast carcinoma. Taken together, our data suggest that during the acquisition of mesenchymal features, the low level of DDR1 expression should be considered as an important biomarker in the prognosis of basal-like breast carcinoma, conferring them a high rate of cell growth and resistance to BIK-mediated apoptosis induced by the stromal collagen.